A new insight into purinergic pharmacology: Three fungal species as natural P2X7R antagonists. (2nd July 2019) - Soares‐Bezerra, Rômulo José; da Silva Ferreira, Natiele Carla; de Almeida Alves, Tânia Maria; Zani, Carlos Leomar; Rosa, Luiz Henrique; Faria, Robson Xavier; da Silva Frutuoso, Válber; Alves, Luiz Anastacio
Abstract : P2X7 is a purinergic receptor involved in important physiological functions and pathological processes, such as inflammation, neurodegeneration, and pain. Despite its relevance, there is no selective antagonist useful in the treatment of diseases related to this receptor. In this context, research for a selective, safe, and potent antagonist compound that can be used in clinical therapy has been growing. In this work, we evaluated the potential antagonistic activity of three fungal extracts, namely, Vishniacozyma victoriae, Metschnikowia australis, and Ascomycota sp., which were discovered in a high‐throughput screening campaign to search for new antagonists for P2X7R from natural products. First, the IC50 values of these fungal extracts were determined in J774.G8 (murine macrophage cell line) and U937 (human monocyte cell line) cells through dye uptake assays. The IC50 values of V. victoriae were 2.6 and 0.92 μg/mL, M. australis has IC50 values of 3.8 and 1.5 μg/mL, and Ascomycota sp. showed values of 2.1 and 0.67 μg/mL in J774.G8 and U937 cells, respectively. These extracts also significantly inhibited propidium iodide and Lucifer yellow uptake via P2X7R pore, P2X7R currents in electrophysiology, IL‐1β release, and the production of oxide nitric and reactive oxygen species. The extracts did not cause cytotoxicity within a period of 24 h. The results showed the promising antagonistic activity of these extracts toward P2X7R, thereby indicating that they can be future candidates for phytomedicines with potential clinical applicability.